OXIDATIVE STRESS AS A PATHOGENETIC LINK OF ACUTE ETHANOL POISONING AND ITS CORRECTION WITH CHELATE ZINC COMPOUNDS - S. I. Kolesnikov; A. V. Mashanov; B. Ya. Vlasov; G. G. Yushkov (Acta Biomedica Scientifica, 2012)
The data on the expressed toxic effect of ethanol in dose DL50 (12 g/kg) on experimental rats were received. The toxic effect was expressed in significant stimulation of processes of lipid peroxidation against the background of antioxidant system suppression. While evaluating the results of statistic analysis it was proved, that new chelate zinc (2,8,9-trihydrozincatrane) in the protective dose of 4 mg/kg under conditions of the acute ethanol poisoning reduces the severity of oxidative stress and normalizes indicators of antioxidant system.